Prática de manualidades com fios e qualidade de vida de mulheres jovens durante a pandemia de COVID-19 - De Marchi, Barbara Frigini (2024)
One of the greatest health challenges of this century, the COVID-19 pandemic has impacted people's quality of life (QoL), especially among younger women who constitute the most vulnerable group. The World Health Organization defines QoL as an individual's perception of their insertion in life, based on the cultural context, values and own goals. This is a multifaceted and subjective topic, related to personal well-being and therefore, also to the flow state. In this context, Positive Psychology deserves to be highlighted, since its constructs have the potential to act as protective factors for mental health, especially in exceptional situations such as the one mentioned. Another contemporary phenomenon concerns the resurgence of textile arts (such as embroidery, crochet and knitting) from the artisanal revolution and do-it-yourself movements, as well as the advent of the pandemic. Despite this, their psychological value has been little explored scientifically. Thus, this research – cross-sectional, essentially quantitative and exploratory-descriptive – aimed to investigate the relationships between the regular practice of textiles arts and the QoL of young women in the context of the COVID-19 pandemic. Participants were 151 Brazilian women aged between 20 and 40 years old who dedicated at least two hours and thirty minutes a week to crafting with yarn. Data collection was conducted in the second half of 2022, through an online survey with a self-generated sample. The instruments used were: a questionnaire developed by the researcher; the Quality of Life Assessment Questionnaire, abbreviated version (WHOQOL-bref); the PERMA-Profiler Flourishing Scale; and the Flow State Scale-2-Crafting (EEF-2-Crafting), which was originally developed for sports practice but was adapted by the researcher for the activity and audience in question, revealing acceptable initial psychometric evidence. The analyses indicated the adequacy of a structure with four dimensions instead of the original nine. The results also showed that women associated textiles arts mainly with sensations and feelings arising from the practice and the various types of these arts. They analyzed the self-assessment and physical domains of QoL better and the psychological domain worse than others. They experienced high levels of well-being, with emphasis on the factors of engagement and positive relationships. Those who have textile arts as a hobby presented higher averages of QoL in the psychological, environmental, and self-assessment domains when compared to those who have them as a source of income. It is expected that this research will contribute to the identification and measurement of the benefits arising from the practice of textile arts, as well as to the understanding of the psychological value of these traditional arts. Additionally, the final product of this research was the development of an educational booklet, which is intended to be distributed to various institutions (educational, health, and social assistance) with the aim of encouraging the practice of these crafts as an effective, accessible and low-cost resource for promoting QoL.